Complex selection of a demulsifier: laboratory studies, numerical simulation and field tests. Issue 2 (4th March 2023) - Yurievich, Ilyushin Pavel; Andreevich, Vyatkin Kirill; Vadimovich, Kozlov Anton
ABSTRACT: The formation of oil-in-water emulsions is one of the main problems in oil production in many oil fields around the world. The transition of exploited fields to the later stages of development exacerbates this complication. The paper presents a method for the complex selection of a demulsifier for in-line demulsification. Laboratory studies were carried out to select the most effective brand and dosage of the demulsifier. Numerical modeling of the influence of the geometrical parameters of the nozzle for the distributed introduction of the demulsifier into the flow on the degree of distribution of the demulsifier in the pipeline section has been performed. As a result of field research at the target object, a 2-fold reduction in the demulsifier dosage was achieved while maintaining pressure in the pipeline. Similar studies were performed for three other objects, where a reduction in reagent consumption by 60, 59 and 25%, respectively, were achieved. The performed study indicates the importance of not only research on the selection of demulsifiers, but also the study of the influence of the method of its introduction into the oil flow to increase the degree of interaction of the reagent with the emulsion being processed.